Impact of endophytic colonization patterns on Zamioculcas zamiifolia stress response and in regulating ROS, tryptophan and IAA levels under airborne formaldehyde and formaldehyde-contaminated soil conditions - Khaksar, Gholamreza (Plant physiology and biochemistry : PPB, 2017)
Copyright © 2017 Elsevier Masson SAS. All rights reserved.